EFFECTS OF LONG-TERM TENNIS PRACTICE ON BONE MASS AND SPINAL ALIGNMENT (University Arena, 2025)
This study examined the effects of prolonged tennis practice on bone mass and spinal alignment in professional and semi-professional athletes. Tennis is a high-impact, asymmetrical sport that may influence skeletal development and posture, particularly in adolescents and young adults engaged in long-term training.Background. Participation in weight-bearing sports is known to increase bone density and improve bone health. However, repetitive, unilateral movements, common in asymmetrical sports like tennis, can lead to muscular imbalances, which may contribute to postural deviations or spinal misalignments. Objectives. There is limited research on how long-term tennis practice affects spinal alignment, particularly among non-professional athletes. This study aims to evaluate differences in spinal alignment among tennis players, investigate whether the duration of tennis practice correlates with specific musculoskeletal adaptations, and explore potential strategies to prevent or mitigate postural imbalances and structural spinal deformities.Methods. A survey-based observational study was conducted involving 30 participants of various ages. The survey included questions about training intensity, the age participants began practicing tennis, duration of practice, as well as self-reported structural conditions, with a particular focus on scoliosis tendencies.Results. Of the 30 respondents, all currently practicing tennis, 13 individuals (43.3%) acknowledged having scoliosis tendencies, while 10 individuals (33.3%) reported experiencing back pain. Notably, two participants were clinically diagnosed with scoliotic posture, both having trained professionally for over a decade. Additionally, one individual, who practiced tennis for over 40 years, reported havingintervertebral disc herniation. Although the sample size was limited, these findings suggest a potential link between repetitive unilateral physical activity and the development of postural asymmetries or structural spinal conditions.Conclusion. Long-term tennis practice is known to enhance bone mass, contributing positively to skeletal health. Nonetheless, it may also lead to asymmetrical spinal adaptations, likely influenced by uneven muscle development and imbalances caused by repetitive unilateral movements. These muscular asymmetries can exert uneven forces on the spine, potentially contributing to postural deviations, highlighting the importance of preventive physiotherapy, kinesiotherapy, and balanced training programs aimed at supporting muscular symmetry and maintaining spinal health.